2018
DOI: 10.1093/jrr/rry077
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics with artificial intelligence for precision medicine in radiation therapy

Abstract: Recently, the concept of radiomics has emerged from radiation oncology. It is a novel approach for solving the issues of precision medicine and how it can be performed, based on multimodality medical images that are non-invasive, fast and low in cost. Radiomics is the comprehensive analysis of massive numbers of medical images in order to extract a large number of phenotypic features (radiomic biomarkers) reflecting cancer traits, and it explores the associations between the features and patients' prognoses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 47 publications
1
58
0
Order By: Relevance
“…Being relatively easy to input data, the most advanced areas with AI technology are diagnostic imaging, followed by genetics [10]. Due to the exponential growth in medical image analyses and pipelines that extract features to be used as valuable decision supporting data, a new practice termed radiomics has emerged [46]. Unfortunately, this trend has been focused on the fields of cancer or diseases related to the cardiovascular or nervous system [10].…”
Section: Discussionmentioning
confidence: 99%
“…Being relatively easy to input data, the most advanced areas with AI technology are diagnostic imaging, followed by genetics [10]. Due to the exponential growth in medical image analyses and pipelines that extract features to be used as valuable decision supporting data, a new practice termed radiomics has emerged [46]. Unfortunately, this trend has been focused on the fields of cancer or diseases related to the cardiovascular or nervous system [10].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning medical imaging, it is theoretically possible to perform many tasks, related to images, through AI techniques, including lesion detection, disease classification, diagnosis and staging, quantification, treatment planning, and assessment of response to treatment and prognosis. 46,47 Recent studies found that radiomics combined with AI provide additional improvements, such as improved operational workflow, financial management, and quality. For example, AI (trained via machine learning) was applied to preoperative MRI studies to distinguish between low-level and high-level tumors using image texture features obtained using multi-mode MRI to achieve World Health Organization (WHO) tumor grading levels.…”
Section: Combining Radiomics With Artificial Intelligencementioning
confidence: 99%
“…There is currently no way to reliably compare between MRI radiomics studies, because variations exist among all of them in MRI scanner sequence, scanner vendor, and scan acquisition parameters (90). We refer the interested reader to comprehensive reviews on the use of radiomics in the field of radiation oncology (90)(91)(92)(93).…”
Section: Tumor Control Probability and Normal Tissue Complication Promentioning
confidence: 99%